A Study on Hospitalized Patients' Payment in South of Iran after the First Round of Health Sector Reform - Kamran BAGHERI LANKARANI; Sulmaz GHAHRAMANI; Behnam HONARVAR (Tehran University of Medical Sciences, 2017)
A Study on Hospitalized Patients' Payment in South of Iran after the First Round of Health Sector Reform